Tantangan Gereja di Era Digital: Model dan Strategi Pendidikan Rohani Anak - Silitonga, Boy Anto Ando; Siagian, Laurenz Enjelina (JURNAL LUXNOS, 2025)
Children's spiritual education is the main foundation in shaping their character and spirituality, with parents as the first educators in the family. However, in the modern era, parental involvement in children's spiritual education is in crisis due to various factors, such as busyness, economy, technology, the influence of secular culture, and a lack of understanding of the importance of spiritual education in the family. This study aims to identify the factors that lead to low parental involvement in children's spiritual education and explore solutions that can be implemented by churches and families. This research was conducted at Kemah Abraham Church Jakarta using a qualitative approach through observation, interview and documentation methods. The data collected was analyzed qualitatively to understand the challenges and strategies to increase parental involvement in children's spiritual education. The results show that several models of approaches that are relevant in the digital era, such as: Modeling, Family Worship, Digital Ministry, and Participatory models, as well as church strategies through faith-based parenting programs, online accessible materials and parental involvement can encourage Christian families to respond to the challenges of the times and maintain the role of the family as the center of children's spiritual education. It provides practical guidance for Christian families in implementing relevant, effective, and contextualized spiritual education in the modern era.